Nitric oxide modulates folate-mediated one-carbon metabolism and mitochondrial energy levels of peaches during cold storage - Yang, Zhifeng; Zhu, Shuhua; Wang, Xiaoyu; Chen, Changbao; Huang, Dandan; Feng, Jianrong (Frontiers in Nutrition, 2023)
Folate, as a nutrient, not only improves yield and fruit quality but also mediates one-carbon metabolism, which regulates fruit ripening. Nitric oxide (NO) regulates physiological and biochemical processes and maintains fruit quality during low-temperature storage. However, folate-mediated one-carbon metabolism (FOCM) information and the regulation by NO on FOCM in postharvest fruit during storage are still scarce. In this experiment, peaches were soaked with 1.5 mmol L−1 S-nitrosoglutathione (GSNO) as NO donor, and the negative treatment (NT) solution containing 5 μmol L−1 carboxy-PTIO (c-PTIO, NO scavenger), 200 µmol L−1 NG-Nitro-L-arginine methyl ester (L-NAME, NO synthase-like enzyme inhibitor), and 200 µmol L−1 sodium tungstate dihydrate (nitrate reductase inhibitor) and stored at 0 °C. The changes in FOCM, storage quality, energy metabolism, and mitochondrial membrane integrity were investigated. Compared with the control, NO decreased the activities of S-adenosyl methionine synthase, S-adenosylhomocysteine hydrolase, increased methionine sulfoxide reductase A activity, and the contents of N5-methyl-THF, tetrahydrofolate (THF), homocysteine, methionine, S-adenosylmethionine (SAM), and the ratio of SAM and S-adenosylhomocysteine, suggesting that NO effectively increased FOCM fluxes by influencing the activities of FOCM enzymes. Meanwhile, NO increased the activities of H+-ATPase, Ca2+-ATPase, cytochrome c oxidase, succinate dehydrogenase, and the contents of adenosine triphosphate and adenosine diphosphate, and maintained high energy charge in peaches during storage. NO retarded the increase in mitochondrial permeability transition, reactive oxygen species content, and the decrease in mitochondrial membrane fluidity, membrane potential, and swelling. NT treatment exhibited the opposite results. These results suggested that NO could induce the accumulation of folate and FOCM flux and maintain mitochondrial energy levels, which might be responsible for maintaining the quality of peaches during cold storage.